Romanian-Yugoslav Relations as Conveyed by Romanian Diplomatic Documents Referring to the Balkan Area (1939) - Miljković, Ema Lj.; Kožokaru, Jonut C. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
One of the most trustworthy partners of Romania was Yugoslavia. Their common purposes, defensive views, as well as the alliances they were part of, reflect this fact. These states, the forms of which were renewed at the end of The First World War, had always wished for the maintainance of peace and development according to the principles of the Peace Treaties of Paris (1919-1920). The Romanian Yugoslav cooperation in the Little Entente and The Balkan Pact represented the desire of the states in this area to settle down, to stop revisionist states’ pretension of reconfiguring the borders. Situated in a restless area, Yugoslavia was compelled to be mindful and on the look out for Fascist Italy’s external politics, especially after the occupation of Albania, while Romania found itself a neighbouring country of Nazi Germany after the latter occupied Czechoslovakia. Our endeavour conducts an analysis of the year 1939 through the eyes of diplomats who struggled to stay neutral and maintain their countries’ territories unaltered.
Keywords: revisionism; Balkan Pact; Little Entente; Romania; Yugoslavia